2021
DOI: 10.53300/001c.21424
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with student satisfaction within a regional student-led physiotherapy clinic: A retrospective qualitative study

Abstract: Clinical education requires students to integrate theoretical knowledge and skills into real-life clinical environments. Most clinical education opportunities remain within metropolitan hospitals where student education is often secondary to patient care. In response, many Universities are developing student-led clinics that focus on the student educational experience, whilst providing high-quality patient care. Understanding factors associated with student satisfaction within student-led physiotherapy clinics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
2
1
0
Order By: Relevance
“…One of the primary goals of many SLCs is to develop clinical skills 4 . This study found that students perceived the SLC as contributing to the development of their clinical skills, which agrees with research by Heales et al, 27 who investigated factors affecting student satisfaction in an Australian student‐led physiotherapy clinic, and a study conducted with physiotherapy students in a student‐led pro bono clinic in the US 18 . Other studies have supported this finding with objective improvement of clinical performance scores for individual physiotherapy students participating in SLCs 32 …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…One of the primary goals of many SLCs is to develop clinical skills 4 . This study found that students perceived the SLC as contributing to the development of their clinical skills, which agrees with research by Heales et al, 27 who investigated factors affecting student satisfaction in an Australian student‐led physiotherapy clinic, and a study conducted with physiotherapy students in a student‐led pro bono clinic in the US 18 . Other studies have supported this finding with objective improvement of clinical performance scores for individual physiotherapy students participating in SLCs 32 …”
Section: Discussionsupporting
confidence: 90%
“…On traditional clinical placements, physiotherapy students are normally supervised during patient contact in a 1:1 or 1:2 model, 26 and although new models are emerging, they are still in their infancy. Participants noted that the 4:1 supervision model in this SLC gave them sufficient space and yet a safe environment for practice, which agrees with research investigating SLCs as a placement by Heales et al 27 and Mosely et al, 24 with the latter operating a 10:1 model of supervision. The findings of this study and the study by Mosely et al 24 would support the premise that a successful and productive learning environment in the form of a SLC can be created with lower ratios of qualified staff to students than is the norm for traditional clinical placements.…”
Section: Discussionsupporting
confidence: 82%
“…Finally, student-led clinics may provide additional learning activities (e.g., supporting sporting and other community events) which reduce the amount of time students are allocated to clinical appointments. These extra-curricular activities, which include observational surgeries, weekly tutorials, and coverage of local sporting events, are appreciated by the students and seen as a positive learning experience (Heales et al, 2021); however, they do come at a cost of less clinic time. Overall, students attending clinical placement within our regional student-led musculoskeletal clinic see on average less total OOS than a musculoskeletal outpatient clinic; however, evidence suggests that students attending student-led clinics may receive additional skills in business management, administration, marketing, and promotion (Moore et al, 2003), as well as benefits to the local community receiving additional access to affordable high-quality health care (Stuhlmiller & Tolchard, 2015).…”
Section: Figure 2 Average Occasions Of Service (Oos) Per Student Per ...mentioning
confidence: 99%